NEEDS ANALYSIS IN LEARNING ENGLISH FOR SPECIFIC PURPOSE (ESP) IN GRAPHIC DESIGN STUDY PROGRAM - Ika Agustina; Rommel Sinaga; Murtopo Murtopo (International Journal of Economy, Education and Entrepreneurship, 2023)
The syllabus for ESP courses must be organized based on the needs analysis (NA) so that the English language learning carried out is relevant to the student's scientific field. NA will also help lecturers to determine appropriate learning methods and media to support ESP learning. This study aims to analyze needs in learning ESP in the Graphic Design study program at Politeknik Negeri Media Kreatif. Needs analysis is carried out using Romanowski's framework, namely Target situation analysis, Present situation analysis, Learning situation analysis, and Mean analysis. A descriptive qualitative approach is implemented in this investigation. The research participants consisted of 34 Graphic Design students and 2 English lecturers. The data collection methods used were a semi-closed-ended questionnaire, and a semi-structured interview. According to the results of the target situation analysis, students require English not only to study but also to meet the expectations of the workplace. They also want the ESP content to be directly related to their major. Students claim in their Learning Situation Analysis that learning ESP will help them advance their careers in graphic design by using a communicative and cooperative approach (including discussion) and practice sessions supported by audiovisual media. The present situation analysis showed that students have a solid grasp of fundamental English but need to improve in a number of areas, especially speaking. The result of means analysis reveals that campuses still do not provide the facilities students expect in ESP course, such as audio-visual equipment, language labs, and ICT-based learning media